(untitled) (Bangladesh Journal of Medical Biochemistry, 2025)
This study explores the link between lipid accumulation product (LAP) and insulin resistance (IR) in 140 seemingly healthy adults (92 males, 48 females) at a Bangladeshi tertiary hospital. IR, a pivotal factor in cardiovascular and metabolic diseases, primarily associated with obesity and visceral fat, is under scrutiny. LAP, derived from waist circumference and triglycerides, is gaining recognition for its ability to reflect metabolic changes related to lipid accumulation. Despite its efficacy in assessing cardiovascular risk and diabetes in diverse populations, there is limited information on LAP’s correlation with IR in Bangladesh context. Anthropometric and physiological measures gauge IR, including LAP, BMI, and WC. Results indicate a robust correlation between LAP and IR, with LAP surpassing BMI and WC, particularly in males. LAP’s continuous variable nature is emphasized, rendering it suitable for population-wide comparisons. Multivariate regression analyses underscore LAP’s more significant impact on HOMA-IR, highlighting its significance in assessing insulin resistance in both genders. The findings contribute to the growing evidence supporting LAP’s superiority in identifying metabolic diseases, cardiovascular risk, and diabetes. LAP emerges as an accessible and straightforward index reflecting anatomical and physiological changes linked to lipid overaccumulation. In conclusion, this study positions LAP as a potent diagnostic tool for recognizing insulin resistance, particularly in large populations, emphasizing its potential utility in the Bangladeshi adult population. Bangladesh J Med Biochem 2021; 14(1): 20-29